TOTAL PRODUCTIVE MAINTENANCE ON THE AIRBUS PART MANUFACTURING - Akbar Adhiutama; Rony Darmawan; Aldo Fadhila (Jurnal Bisnis Manajemen, 2020)
An Indonesia manufacturing company producing Airbus wing parts experienced losses of more than $100,000 in 2017. The production of A 380 wing parts contributed to 73% of the total losses, and 37% came from parts production of A 350 and A 320. The study focused on the most significant contribution losses of A 380 wing parts that is Drive Rib 1.  This paper aims at examining the root cause of the loss in A 380-Program, solving the root cause by proposing the alternative solution, and improving the performance in A 380 Program. By conducting the interview and archival data, the data were analyzed employing Root Cause Analysis (RCA) to discover the root cause of problems. Low reliability of the production machine (DGAL Cincinnati Milacron) was identified as a root cause indicated by Overall Equipment Effectiveness (OEE) at 50.3% used since the 1980s. According to Total Productive Maintenance (TPM), this study proposes three alternative business solutions (autonomous maintenance, quality maintenance, and machine replacement). By considering the results of OEE and Analytical Hierarchy Process (AHP) with three criteria (cost, benefit, and implementation), the problem-solution proposes two approaches, namely conducting the autonomous maintenance with an improvement of OEE about 7% for the short term period and organizing the machine replacement with a significant OEE improvement about 17.1%.